Eksploitasi Perempuan di Ranah Digital dalam Perspektif Tafsir Al-Mishbah Karya M. Quraish Shihab - Dzakiyyah Agustira Soleh Jamil; Abd. Muid Nawawi; Nurbaiti Nurbaiti (International Journal Labs, 2026)
This study aims to describe the exploitation of women in the digital era and analyze it through the science of tafsir, as well as the Islamic perspective on women in digital media. The media exploits the gender equality women are fighting for for business interests, but often ignores religious norms, degrading women's dignity. Islam values ??women, and the media's treatment of them is not respectful, but rather insulting. Throughout Islamic history, scholars have paid attention to women's issues, including M. Quraish Shihab who discussed the role of women in his commentary, Tafsir Al-Mishbah. This study uses qualitative methods (library research) and descriptive analysis to uncover M. Quraish Shihab's thoughts on gender equality and the role of women. The results show that M. Quraish Shihab emphasizes the equal dignity and rights of men and women, rejecting views that demean women or equate them without considering their natural nature. He views natural differences as a form of complementarity and emphasizes that women have equal rights to contribute intellectually, spiritually, and socially. M. Quraish Shihab criticizes the exploitation of women by the media and reminds women to maintain their dignity in utilizing their potential while still respecting norms of decency and socio-religious responsibilities.